Makna Pragmatik Tuturan Lisan Tuara Penjemputan Hasil Panen Masyarakat Wewewa Sumba Barat Daya - Kami, Kanisius; Kaleka, Lasarus Bulu; Kette, Mateus; Manek, Milka Gloryani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The aim of this research is to describe the pragmatic meaning contained in the oral speech of tuara picking up the harvest of the Wewewa community of Southwest Sumba. This type of research is descriptive qualitative research which produces data in the form of written or spoken words from people or observable behavior. The data collection techniques in this research are expert listening and recording techniques. In the active listening technique, the researcher listens and is involved in the conversation with the traditional elders, while in the recording technique, the researcher records the entire process of the conversation with the traditional elders. The data analysis technique is carried out by following three stages, namely the data reduction stage, the data presentation stage, and the conclusion stage. Based on the analysis of the pragmatic meanings in the oral speech about picking up the harvest, it was concluded that there are three meanings, namely the meaning of preparing, greeting and begging